Cover Image. Issue 9 (September 2017) - Brinkman, P.; van de Pol, M. A.; Gerritsen, M. G.; Bos, L. D.; Dekker, T.; Smids, B. S.; Sinha, A.; Majoor, C. J.; Sneeboer, M. M.; Knobel, H. H.; Vink, T. J.; de Jongh, F. H.; et al.
Abstract : The cover image, by P. Brinkman et al., is based on the Original Article Exhaled breath profiles in the monitoring of loss of control and clinical recovery in asthma, DOI:10.1111/cea.12965 .